Raman imaging of microbial colonization in rock-some analytical aspects - Vítek, Petr; Ascaso, Carmen; Artieda, Octavio; Casero, M Cristina; Wierzchos, Jacek (Analytical and bioanalytical chemistry, 2020)
Raman imaging allows one to obtain spatially resolved chemical information in a nondestructive manner. Herein, we present analytical aspects of effective in situ and in vivo Raman imaging of algae and cyanobacteria from within their native rock habitats. Specifically, gypsum and halite inhabited by endolithic communities from the hyperarid Atacama Desert were analyzed. Raman imaging of these phototrophic colonization reveals a pigment composition within the aggregates that helps in understanding some of their adaptation strategies to survive in this harsh polyextreme environment. The study is focused on methodical aspects of Raman imaging acquisition and subsequent data processing. Point imaging is compared with line imaging in terms of their image quality, spatial resolution, spectral signal-to-noise ratio, time requirements, and risk of laser-induced sample alteration. The roles of excitation wavelength, exposure time, and step size of the imaging grid on successful Raman imaging results are also discussed. Graphical abstract.
Keywords: Ramanova spektroskopie; sinice; Geobiology; Pigments, Biological; Astrobiology; Image analysis; Soil Microbiology; pouštní klima; Cyanobacteria; Raman mapping; Scytonemin; Desert Climate; Spectrum Analysis, Raman; Bioimage; biologické pigmenty; půdní mikrobiologie; ekosystém; Ecosystem